As necessidades formativas de educadores sociais: desafios e possibilidades na formação em serviço em uma organização da sociedade civil - Salvador, Mercia Simões da Silva (2020)
The present study proposed to investigate the training needs of social educators who work from the perspective of non-formal education of children and teenagers in a civil society organization in the municipality of Diadema/ SP. The research uses a qualitative approach, the data were obtained through semi-structured interviews conducted in a group with four social educators, submitted to content analysis.The study is justified because it is a little explored topic and Gohn’s studies on non-formal education and the role of the social educator in Brazil were used, such as studies by Imbernón and Paulo Freire, considering an outline for in-service training of social educators. We sought to identify training needs, the challenges and problems faced in the possibilities of coping in their daily practice were the object of analysis and reflection with the group, in a process of developing shared service training. The group listed the need for in-service training with time to share planning and activities and study consultation materials to understand the work focused on the program of the partnership with the city. They also discussed the challenge in the relationship between students and working with heterogeneous groups. The results demonstrate that when proposing intentional moments for reflection and exchange of experiences among social educators, through the analysis of their training needs, the autonomy of educators is evident in relation to their positioning for the necessary changes in their educational practice with the students. At the end of this investigation, it is emphasized that in-service training dialogues as a facilitator for the professional development of social educators